# 10 – 10 =9 – 9 = 8 – 8 =7 – 7 = 6 – 6 =5 – 5 = 0 + 5 = 1 + 4 = 2 + 3 = 0 + 6 = 1 + 5 = 2 + 4 =

## Presentation on theme: "10 – 10 =9 – 9 = 8 – 8 =7 – 7 = 6 – 6 =5 – 5 = 0 + 5 = 1 + 4 = 2 + 3 = 0 + 6 = 1 + 5 = 2 + 4 ="— Presentation transcript:

10 – 10 =9 – 9 = 8 – 8 =7 – 7 = 6 – 6 =5 – 5 = 0 + 5 = 1 + 4 = 2 + 3 = 0 + 6 = 1 + 5 = 2 + 4 =

4 – 4 =3 – 3 = 2 – 2 = 0 – 0 = 10 – 9 = 1 – 1 = 3 + 2 = 3 + 3 = 4 + 2 = 0 + 10 =1 + 9 = 2 + 8 =

9 – 8 =8 – 7 = 7 – 6 =6 – 5 = 5 – 4 =4 – 3 = 4 + 1 = 5 + 0 = 5 + 1 = 6 + 0 = 3 + 7 =4 + 6 =

3 – 2 =1 – 0 = 10 – 8 =9 – 7 = 8 – 6 = 7 – 5 = 0 + 7 = 1 + 6 = 2 + 5 =3 + 4 = 4 + 3 = 9 + 0 =

6 – 4 =5 – 3 = 4 – 2 =3 – 1 = 2 – 0 =10 – 7 =7 + 0 = 6 + 1 = 7 + 2 = 8 + 1 = 5 + 5 = 6 + 4 =

9 – 6 = 8 – 5 =7 – 4 = 6 – 3 = 5 – 2 = 10 – 0 = 0 + 4 = 1 + 3 = 7 + 1 = 5 + 4 = 6 + 3 = 7 + 3 =

4 – 1 =3 – 0 = 10 – 6 =9 – 5 = 8 – 4 = 7 – 3 = 0 + 3 = 1 + 2 = 0 + 8 = 1 + 7 = 8 + 2 = 0 + 0 =

5 – 1 =4 – 0 = 10 – 5 = 9 – 4 = 6 – 2 =2 – 1 = 0 + 1 = 1 + 0 =2 + 1 = 2 + 6 = 3 + 5 =4 + 5 =

8 – 3 =7 – 2 = 6 – 1 =5 – 0 = 10 – 4 =9 – 3 = 3 + 0 = 8 + 0 = 2 + 7 = 3 + 6 = 10 + 0 = 3 + 1 =

8 – 2 =7 – 1 = 6 – 0 =10 – 3 = 9 – 2 =8 – 1 = 4 + 4 = 5 + 3 = 6 + 2 = 9 + 1 = 4 + 0 = 5 + 2 =

7 – 0 =10 – 2 = 9 – 1 =8 – 0 = 10 – 1 =9 – 0 = 0 + 2 = 1 + 1 =2 + 0 = 2 + 2 = 0 + 9 =1 + 8 =

Similar presentations